(3GdGSJQGJjLjGJ GdeJHYI aj GdJMVjQ GdHOfj ddhbGjI hGdJfHD HGdEUGHGJ GdQjGVjI dOi dGYHj cQI GdbOe (B: (3OQGSI ejOGfjI Ydi HYV GfOjI GdbSe GdhWfj GdKGfj ghGI (B-s - (3chQOGS , NGdOs; (3MGLj, eMeO GdYQHjs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2023)
(3gOaJ gPg GdOQGSI Gdi eYQaI eG EPG cGfJ GdGSJQGJjLjGJ GdeJHYI aj GdJMVjQ GdHOfj JSGYO Ydi GdhbGjI hGdJfHD HGdEUGHGJ GdQjGVjI NdGd GdehSe dOi dGYHj cQI GdbOe? JeKd eLJeY GdOQGSI ef dGYHj GdaQjb GdQOja Ufa (BU21 (3h GdeOQHjf h GdeMVQjf GdHOfjjf GdJGHYjf ddbSe GdhWfj GdKGfj HhGbY (B32 (3fGOj, hTedJ YjfI GdOQGSI (B76 (3dGYHG Ufa BeGd (BU21 (3ef GJMGO NfTdI, MeQGA YfGHI, ehdhOjI bSfWjfI h (B35 (3eOQH heMVQ HOfj JGHYjf ddbSe GdhWfj GdKGfj ghGI GdehSe GdcQhj (B(2021-2022)(3, Je GNJjGQge HGdWQjbI GdYeOjI , Je GSJNOGe GdefgL GdhUaj befG ChdG HbjGS GddGYHjf YfO HOGjI eQMdI GdJMVjQ GdHOfj aj cd ef (B: (3GdbOQI GdYVdjI (B((3Se(B.J,SJ)(3,GdeQhfI ,GdJhGRf , TGTI GdMQcI GdhXjajI Ke HYO fgGjI GdeQMdI GdJMVjQjI befG HbjGS HYOj dfaS GdGNJHGQGJ HGSJKfGA GNJHGQ (BFMS (3eY eJGHYI ddEUGHGJ HeSGYOI GdWGbe GdWHj NdGd GdehSe, CjVG bGe GdHGMK HJhRjY GSJHjGf Ydi GdeOQHjf h GdeMVQjf GdHOfjjf deYQaI GdeeGQSGJ GdMGdjI dOi GfOjI cQI GdbOe ajeG jJYdb HGSJQGJjLjGJ GdhbGjI ef GdEUGHGJ GdQjGVjI ZjQ GdGMJcGcjI (B(sans contact) (3ef MjK(B: (3JNWjW hJfajP eMJhi HQfGeL GdhbGjI, GdWGbe GdeTGQc aj HQfGeL GdhbGjI hGdGNJHGQGJ GdhbGFjI, JhUd GdHGMK Gdi Gf GdGSJQGJjLjGJ GdeJHYI aj GdJMVjQ GdHOfj JSGYO Ydi GdhbGjI h GdJfHD HGdEUGHGJ GdQjGVjI dOi dGYHj cQI GdbOe (B. s
(3OcJhQGIs
Keywords: (3GdEUGHGJ GdQjGVjIs; (3GdJMVjQ GdHO fjs; (3GdJMVjQ GdHOfj GdQjGVjs; (3cQI GdbOes